Diversity and Distribution Characteristics of Viruses in Soils of a Marine-Terrestrial Ecotone in East China - Yu, Dan-Ting; Han, Li-Li; Zhang, Li-Mei; He, Ji-Zheng (Microbial ecology, 2018)
A substantial gap remains in our understanding of the abundance, diversity, and ecology of viruses in soil although some advances have been achieved in recent years. In this study, four soil samples according to the salinity gradient from shore to inland in East China have been characterized. Results showed that spherical virus particles represented the largest viral component in all of the four samples. The viromes had remarkably different taxonomic compositions, and most of the sequences were derived from singlestranded DNA viruses, especially from families Microviridae and Circoviridae. Compared with viromes from other aquatic and sediment samples, the community compositions of our four soil viromes resembled each other, meanwhile coastal sample virome closely congregated with sediment and hypersaline viromes, and high salinity paddy soil sample virome was similar with surface sediment virome. Phylogenetic analysis of functional genes showed that four viromes have high diversity of the subfamily Gokushovirinae in family Microviridae and most of Circoviridae replicase protein sequences grouped within the CRESS-DNA viruses. This work provided an initial outline of the viral communities in marine-terrestrial ecotone and will improve our understanding of the ecological functions of soil viruses.